2009
DOI: 10.1890/090062
|View full text |Cite
|
Sign up to set email alerts
|

Do birds affect Lyme disease risk? Range expansion of the vector‐borne pathogen Borrelia burgdorferi

Abstract: Because of their capacity for long‐range movement, birds may play an important role in the spread and range expansion of zoonotic pathogens and their vectors. The black‐legged tick (Ixodes scapularis) is the principal vector for the Lyme disease bacterium Borrelia burgdorferi, and commonly parasitizes a wide variety of vertebrate hosts, including at least 71 species of North American birds. Although the role of birds in B burgdorferi transmission dynamics is often discounted, data compiled from published studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 47 publications
1
88
0
Order By: Relevance
“…Testing for B. burgdorferi in our study was not performed to identify vectors but rather to potentially learn about enzootic maintenance of the pathogen in local or migratory birds and their ticks, given that spirochetes in the avian blood could have been detected by our approach of testing the blood directly or testing the engorged ticks. Birds play a key role in the ecology of Lyme disease through contributing to the range expansion of ticks and maintaining B. burgdorferi in the environment in areas where Lyme disease is recognized as endemic or emerging (4,26,(68)(69)(70). Regional studies of pathogen prevalence are increasingly important from ecological and human health perspectives, especially considering that the annual movement patterns of many of the birds connect geographic zones in which Lyme disease is endemic with those in which it is nonendemic.…”
Section: Discussionmentioning
confidence: 99%
“…Testing for B. burgdorferi in our study was not performed to identify vectors but rather to potentially learn about enzootic maintenance of the pathogen in local or migratory birds and their ticks, given that spirochetes in the avian blood could have been detected by our approach of testing the blood directly or testing the engorged ticks. Birds play a key role in the ecology of Lyme disease through contributing to the range expansion of ticks and maintaining B. burgdorferi in the environment in areas where Lyme disease is recognized as endemic or emerging (4,26,(68)(69)(70). Regional studies of pathogen prevalence are increasingly important from ecological and human health perspectives, especially considering that the annual movement patterns of many of the birds connect geographic zones in which Lyme disease is endemic with those in which it is nonendemic.…”
Section: Discussionmentioning
confidence: 99%
“…The American Redstart was my control species because this species may not be able to support the pathogen because at least two tick larvae were tested and were not infected with the pathogen (Brinkerhoff et al 2011). However, the study found that there was a positive relationship between the number of American Redstarts observed and Lyme disease rate for 008 Woodbury and 012 Warren.…”
Section: Resultsmentioning
confidence: 99%
“…The role of birds in Lyme disease could be very large (Brinkerhoff et al, 2011) stated that ticks derived from birds can influence B. burgdorferi transmission dynamics, either "by establishing new enzootic Lyme disease foci through the deposition of infected larval ticks … or by dispersing infected larvae or nymphs that would then molt and parasitize humans.…”
mentioning
confidence: 99%
“…Although birds, small mammals, and lizards are all natural reservoirs of B. burgdorferi sensu lato (Bbsl), birds may play a key role in the dissemination and spatial distribution of Borrelia, notably as a result of their migratory behavior (Olsen et al 1993, 1995, Kurtenbach et al 1998, Comstedt et al 2006, Duneau et al 2008, Brinkerhoff et al 2009, Dubska et al 2009). Seabirds may be particularly important in the global circulation of LB spirochetes (Olsen et al 1995); these birds are widely distributed and breed in large groups that often include a diverse range of interacting species (Schreiber and Burger 2001).…”
Section: Introductionmentioning
confidence: 99%